Advertising: The contribution of applied cognitive psychology. Issue 2 (13th September 2018) - Furnham, Adrian
Summary: This paper looks at the contribution of applied cognitive psychology primarily to the research on advertising. The first issue is to attempt to define and specify the unique contribution of applied, as opposed to "pure, " cognitive psychology to this research area. Next, the issue of the medium of message delivery is discussed. The importance of program involvement and mood impact on memory for advertisements is then reviewed. The major part of the review looks at the influence of humor, sex, violence, and unconventional sex roles in advertisements on their impact on viewer's memory. An attempt is made to document important and replicated findings in this area. Finally, some effort is made to consider future avenues of research.